Media Stupa Merah Putih Bermagnet untuk Meningkatkan Hots dan Hasil Belajar dalam Penguatan Pendidikan Karakter - Fajriyatun, Fajriyatun; Saliman, Saliman (Jurnal Didaktika Pendidikan Dasar, 2018)
Teachers must be able to innovate in learning that can create appropriate and visionary learning. This condition is the background of the research on learning innovation using the media of the Red and White Magnetic Stupa. The aims of this study was to describe the results of learning innovations using the media of Magnetic Red and White Stupa in Improving High Order Thinking Skills (HOTS) and learning outcomes of VIIG class students at SMP Negeri 1 Rakit. This research is included in the type of classroom action research, with the subjects of the research of teachers and students of class VIIG SMP Negeri I Rakit, and research objects in the media of the Red and White Magnetic Stupa. Data collection using test techniques and data analysis is done qualitatively and qualitatively. The results showed 93% of students increased in the application of HOTS, learning outcomes increased, where 85% of students showed complete learning with an average value of 79.67. Thus it can be said that learning using media Magnetic Red and White Stupa can increase HOTS, learning outcomes, and in the end can strengthen students' character.